Penerapan Media Digital Interaktif Berbasis Aplikasi Kahoot untuk Meningkatkan Pemahaman Konsep Siswa SDN Ngasemlemahbang - Tusida Sherlina Dewi; Humairah Humairah; Arfian Mudayan (Universitas Negeri Medan, 2025)
This study aims to improve students' conceptual understanding. This type of classroom action research implements interactive digital media based on the Kahoot application. The subjects of the study were all fourth-grade students at SDN Ngasemlemahbang, totaling 16 students. Each cycle consisted of the stages of planning, implementation, observation, and reflection. The data analysis techniques used were observation result analysis and conceptual understanding analysis. The results of the study can be concluded as follows: (1) Teacher activity observation in Cycle I obtained an average score of 62.5%, and in Cycle II, it increased to 88.67%, showing an improvement of 26.17%. (2) Student activity observation in Cycle I obtained an average score of 58.33%, and in Cycle II, it increased to 89.16%, indicating an improvement of 30.83%. (3) Students’ conceptual understanding in Cycle I reached 56.25%, and in Cycle II, it increased to 81.25%, showing an improvement of 25%. Therefore, it can be concluded that the use of the Kahoot application in learning activities can improve students’ conceptual understanding in the topic of two-dimensional shapes in the fourth grade at SDN Ngasemlemahbang.